Cognitive fatigue effects on physical performance: the role of interoception - McMorris, T. (Sports Medicine, 2020)
The consensus of opinion, with regard to the effect of cognitive fatigue on subsequent physical performance, is that there is a small, negative effect, but there is no consensus regarding the mechanisms involved. When glucose levels are normal, undertaking cognitive tasks does not induce energy or neurotransmitter depletion. The adenosine hypothesis is questioned as cognitively induced increases in adenosine release are phasic and transient, while persistent effects of adenosine are tonic. Thus, the most likely explanation for a negative effect of cognitive fatigue would appear to be changes in perceptions of effort, for which there is some evidence from subjective participant feedback, while interoceptive theory would suggest a role for motivation levels. Cognitive fatigue and physical fatigue are dependent on interoceptive mechanisms, in particular the interactions between top-down predictions of effort from the dorsolateral prefrontal cortex (PFC) to the insula cortex, anterior cingulate cortex, ventromedial and ventrolateral PFC, and bottom-up feedback from the lamina I spinothalamic pathway, and the vagal and glossopharyngeal medullothalamic pathway. The dopaminergic mesocorticolimbic and the locus coeruleus-noradrenaline pathways are also vital. It would appear that cognitive fatigue leads to different predictions of the expected sensory consequences of undertaking the exercise than in the control condition and there is some evidence that motivation can overcome this. Much more research, in which motivation levels are manipulated, is necessary as the effects are small and the reasons for cognitive fatigue causing changes in predictions of sensory consequences are not clear.